Assessing levels and seasonal variations of current-use pesticides (CUPs) in the Tuscan atmosphere, Italy, using polyurethane foam disks (PUF) passive air samplers. (October 2015) - Estellano, Victor H.; Pozo, Karla; Efstathiou, Christos; Pozo, Katerine; Corsolini, Simonetta; Focardi, Silvano
Abstract: Polyurethane foam disks (PUF) passive air samplers (PAS) were deployed over 4 sampling periods of 3–5-months (≥ 1 year) at ten urban and rural locations throughout the Tuscany Region. The purpose was to assess the occurrence and seasonal variations of ten current-use pesticides (CUPs). PUF disk extracts were analyzed using GC–MS. The organophosphates insecticides; chlorpyrifos (3–580 pg m −3 ) and chlorpyrifos-methyl (below detection limit – to 570 pg m −3 ) presented the highest levels in air, and showed seasonal fluctuation coinciding with the growing seasons. The relative proportion urban/(urban + rural) ranged from 0.4 to 0.7 showing no differences between urban and rural concentrations. Air back trajectories analysis showed air masses passing over agricultural fields and potentially enhancing the drift of pesticides into the urban sites. This study represents the first information regarding CUPs in the atmosphere of Tuscany region using PAS-PUF disk. Highlights: Current use pesticides (CUPs) were detected in the atmosphere of Tuscany, Italy. Chlorpyrifos showed the highest concentrations in air with seasonal patterns. CUPs levels might be influenced by agricultural activities. No differences were detected between Urban and Rural sites. Air mass analysis indicated the monitoring sites are influenced by local sources. Abstract : Seasonality of CUPs was measured in Tuscany, Italy. Chlorpyrifos showed the highest values. Urban and rural sites showed no differences. Agricultural activities influence CUPs levels in air.